Oil Palm Empty Fruit Bunches Fiber-Supported Heterogeneous Acid Catalyst for Esterification of Oleic Acid: Effect of Different Transition Metal Sulfate - Gowri Krishnan, Shamala; Pua, Fei-ling; Palanisamy, Kumaran; Nabihah Syed Jaafar, Sharifah; Subramaniam, Koguleshun (International Journal of Engineering and Technology, 2018)
This paper presents the investigation of oil palm empty fruit bunch (EFB) fiber-supported heterogeneous acid catalyst that was prepared via direct impregnation method by using various types of transition metal sulfates, including Fe2(SO4)3, NiSO4.6H2O, and CuSO4. The EFB fiber-supported heterogeneous acid catalyst was applied for esterification of oleic acid. Hence, structural, chemical, morphological, and elemental properties of the catalyst were examined through the use of X-ray diffraction (XRD), Fourier transform infrared (FTIR), scanning electron microscope (SEM), and electron dispersive X-ray spectroscopy (EDX) analyses. Meanwhile, the acidity properties of each catalyst were characterized via acid density test. The prepared catalyst, which had been loaded with Fe2(SO4)3, exhibited the highest acid density up to 2.4 mmol/g. Next, the catalytic activity of the heterogeneous acid catalyst was further investigated through esterification of oleic acid at 60Â°C with 5 wt% catalyst loading for 2 hours of reaction time. The prepared catalyst, which was loaded with Fe2(SO4)3, again displayed the high esterification conversion rate at 93.90% and was used up to five reaction cycles.Â